2013
DOI: 10.1097/cej.0b013e32835f3be9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of plasma microRNAs as novel noninvasive biomarkers for early detection of lung cancer

Abstract: Recent diagnostic procedure advances have considerably improved early lung cancer detection. However, the invasive, unpleasant, and inconvenient nature of current diagnostic procedures limits their application. There is a great need for novel noninvasive biomarkers for early lung cancer diagnosis. In the present study, we aimed to determine whether microRNA (miRNA) blood signatures are suitable for early detection of lung cancer. Using quantitative reverse transcriptase PCR analysis, we first selected and iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(87 citation statements)
references
References 28 publications
1
86
0
Order By: Relevance
“…These reports have characterized miR-21, miR-155 and miR-18a (miR-17-92 cluster) as oncogenic miRNAs (oncomirs) [Lu et al, 2011;Lu and Rothenberg, 2013]. The expression of these oncomirs has been associated directly with increased lung cancer severity in humans [Volinia et al, 2006;Tang et al, 2013;Yang et al, 2013]. The activation of specific oncomirs raises a new question: are individuals who were exposed to SHS in utero at heightened risk as adults for certain cancers?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These reports have characterized miR-21, miR-155 and miR-18a (miR-17-92 cluster) as oncogenic miRNAs (oncomirs) [Lu et al, 2011;Lu and Rothenberg, 2013]. The expression of these oncomirs has been associated directly with increased lung cancer severity in humans [Volinia et al, 2006;Tang et al, 2013;Yang et al, 2013]. The activation of specific oncomirs raises a new question: are individuals who were exposed to SHS in utero at heightened risk as adults for certain cancers?…”
Section: Discussionmentioning
confidence: 99%
“…1.2E-03 Asthma Winkler et al, 2014;Wu et al, 2014], Cancer [Seike et al, 2009;Tang et al, 2013;Yang et al, 2013], $: "2.0 #: "2.4* miR-298-5p 1.2E-03 $: "2.0* #: "2.5* miR-341-3p…”
Section: Tumor Suppressor Genes Predicted Targets Of the Activated Omentioning
confidence: 99%
See 1 more Smart Citation
“…A panel of 5 miRNAs, including 3 with increased plasma concentrations (miR-21-5p, -182-5p, and -210-3p) and 2 with decreased concentrations (miR-126-3p and -486-5p) provided good diagnostic power for all stages of NSCLC (43,44 ). Additionally, the increased miR-21-5p and -155-5p and decreased miR-145 concentrations in plasma also showed good diagnostic potential in differentiating patients with NSCLC from healthy smokers (45,46 ). Although it is not included in our analysis, the change in concentration of specific circulating miRNAs has also been reported as a prognostic marker.…”
Section: Lung Cancermentioning
confidence: 97%
“…It has been proven that small noncoding RNAs, including micro-RNAs, shows great stability in the circulation with the state of microRNA-processing proteins (47). The micro-RNAs have oncogenic and tumor suppressor gene function and exhibit specific expression profiles in lung cancer, and thus have been proposed as diagnostic and prognostic markers (48)(49)(50)(51). In particular, the work of Montani et al identified a signature of several plasma microRNA that showed an excellent predictive value for lung cancer in a high-risk population (52).…”
Section: Circulating Nucleic Acidsmentioning
confidence: 99%